Significance of Protection of Human Rights for Crime Prevention - Sadiković, Lada (Kriminalističke teme, 2004)
On 12. th of July 2002. Bosnia and Herzegovina has ratified the European convention for protection of human rights. Our State has accepted not only the rights of Convention but the whole European mechanism for protection of human rights. In this case special meaning have those rights, that obligates the state Bosnia and Herzegovina to create and to promote judiciary, but also the whole other state’s institutions, which the basic purpose is to prevent every form ofcrime.